Soluble and insoluble fibre sources in weaning piglets’ diets Fibras solúvel e insolúvel em dietas de leitões na creche - Spagnol R.S. (2024)
© 2024, Universidade de Sao Paulo. Faculdade de Medicina Veterinaria e Zootecnia. All rights reserved.This study evaluated the effect of diets containing low levels of soluble and insoluble fiber sources on performance, diarrhea score, chemical and physical characteristics of feces, and behavior in weaning piglets. Thirty-six weaned piglets of 30 days of age with an initial body weight of 8.8 kg were distributed in 36 pens using a completely randomized design in an experimental period of 21 days. The experimental treatments were the Control diet (CONT), the Control diet + 1% beet pulp inclusion (SBP), and the Control diet + 1% lignocellulose inclusion (LCE, Arbocel®). Feed and water were available ad libitum. Body weight and feed intake were measured weekly to calculate the average daily intake, weight gain, and feed conversion ratio. The fecal consistency was determined visually twice daily, classifying feces according to three scores. To determine fecal pH and concentration of fecal short-chain fatty acids (SCFA), samples of fresh feces were collected two weeks after weaning and measured by a digital pH meter and gas chromatography, respectively. The behavior of piglets was observed once a week, using four animals per treatment, from 14:00 to 16:00, every 12 min. Fibre sources had no effect (P>0.05) on performance, except in the period 15 to 21 days after weaning, which was a tendency (P=0.061) of feed intake decrease in SBP and LCE diets. Fiber sources did not affect the fecal consistency score (P>0.05). However, piglets fed SBP and LCE showed a tendency (P<0.10) to have less diarrhea incidence 15 to 21 days post-weaning and in the entire experimental period. Fecal pH and SCFA concentration were not influenced by fiber source (P>0.05), with acetic, propionic, and butyric acids representing around 71%, 19%, and 10% of the total, respectively. Fiber sources did not influence the social and feeding behavior of weaning piglets (P>0.05). Diets containing 1% fiber sources did not alter performance, diarrhea score, fecal pH, fecal SCFA concentration, or feeding and social behavior of weaned piglets.